HEAT PUMPS AND COST OPTIMAL BUILDING PERFORMANCE - Gjerkeń, Henrik; Zavrl, Marjana Ńijanec; Stegnar, Gańper (European Scientific Journal, ESJ, 2014)
Slovenia has established comparative methodology framework for the minimum energy performance requirements on the basis of article 5 of the Directive EPBD – Recast (2010/31/EU) and in accordance with Annex III, differentiating between different categories of buildings. Choosing a single family house, energy performance of the buildings was calculated with IDA Indoor Climate and Energy as a whole year detailed and dynamic multizone simulation study of indoor climate and energy use. The minimum energy performance requirements are represented by the area of the cost curve that delivers the lowest cost for the end-user and society. The results demonstrate that the minimum requirements set for new single family houses in national building codes in force are more severe than the minimum requirements corresponding to the cost optimal level, mainly due to the national energy and climate policy targets in the building sector. Among systems, heat pumps proved to be important competitors in seeking the cost optimal building performance. It was shown, that heat pumps are environmentally acceptable and economically efficient way of heating with plausible positive social multiplied effects. Heat pumps have support of local economy and are based on well-established technology, their operational is efficient, reliable and are suitable for almost all buildings. In the future it is expected to reach higher coefficient of performance (COP), especially at lower temperatures. Higher COP, together with further increase of renewables share in national electrical power system is making heat pumps important foundation for further sustainable development in line with sustainable principles.